IMPLEMENTASI APLIKASI KASIR BERBASIS WEBSITE PADA USAHA LAUNDRY RUMAH HANA - Salam, Riyan Ikhbal; Eka Putra, Dian; Djasmayena, Selvia (Jurnal Teknologi Komputer dan Informasi, 2024)
Laundry Rumah Hana is a service business providing washing and ironing services. Currently, Laundry Rumah Hana manages transactions and financial reports manually using notebooks, which makes it highly susceptible to errors in transactions and financial reporting. The rapid advancement of technology necessitates the use of technology in managing transactions and financial reports for laundry businesses. A web-based cashier application is seen as a strategic step to improve operational efficiency and expand market reach through a digital platform. The web-based cashier application enables online management of transactions, customer information, and financial reports. This study aims to design a responsive cashier application by integrating essential features such as financial reporting and secure online payment methods. The research method used in this study is the waterfall method. The web-based cashier application for Laundry Rumah Hana is expected to enhance service quality, speed up the transaction process, and facilitate financial reporting. This application will provide significant benefits in improving the management of the laundry business, thereby helping it remain competitive in an ever-evolving market